Strategi Peningkatan Rantai Pasok UMKM Repro dengan Pendekatan Interpretive Structural Modelling - Sari, Lidia Puspita; Aulia, Arshinta Wilda; Talitha, Tita (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The maggot cultivation industry managed by Repro MSMEs experiences various challenges such as, there is no integration between supply chain actors and Repro MSMEs are directly involved as producers and retailers because they market directly without going through intermediaries. The research respondent is an expert in the supply chain field totaling 5 people, data collection is carried out by a brainstorming process then Focus group discussion (FGD) and through a closed questionnaire. This research aims to create a strategy to improve the supply chain that is comprehensive and data-based in order to be more optimal. The ISM method is a strategic decision-making step to identify the interrelationships between the most influential variables. ISM data processing uses the help of ISM Professional 2.0 software. This research has successfully identified and modeled supply chain strategies from ten variables. Based on ISM modeling, the most significantly influential variable is variable A1, and at the top level is variable A9, this means that variable A9 becomes an entity with a low level of urgency. This research is expected to facilitate MSME owners to make decisions in determining priorities as a reference for implementing strategies that must be used in optimizing the supply chain system. Keywords: Interpretive Structural Modeling, MSMEs, Supply Chain